Investigating the Inhibitory Effects of Some Alkaloid Compounds against Aflatoxin Biosynthesis Polyketide Synthase by Molecular Docking Method - SarveAhrabi, Yasin; Nejati Khoei, Sarina; Bayat, Mansour (Archives of Advances in Biosciences, 2024)
Introduction: Aflatoxins are toxic metabolites produced by certain fungi, primarily Aspergillus species, that contaminate various food and feed crops. Alkaloids, a diverse group of naturally occurring compounds found in plants, animals, and microorganisms, have been investigated as potential inhibitors of polyketide synthase in aflatoxin biosynthesis. The purpose of this study is to investigate the inhibitory potential of a few alkaloid compounds against aflatoxin biosynthesis polyketide synthase. Materials and Methods: The 2D structures of 10 alkaloid compounds, used as ligands, were obtained from PubChem database and optimized using the MM2 Job command in Chem3D Pro 12.0.2.1076 software. The ligands were assessed as inhibitors against the active site of the aflatoxin biosynthesis polyketide synthase protein using AutodackVina software. The results were analyzed using Discovery Studio v16.1.0 software. Results: Among the compounds studied, atropine, hyoscyamine, morphine, and strychnine exhibited the highest binding affinities with values of -11.9, -10.8, -11.5, and -11.1 kcal/mol, respectively, for the 3HRR (aflatoxin biosynthesis polyketide synthase) protein. Additionally, neurocaine and morphine demonstrated notable binding affinities of -11.6 and -12.9 kcal/mol, respectively, for the 3HRQ (Biosynthetic) protein. Notably, morphine displayed the strongest inhibitory activity against both proteins, with key amino acids aspartic acid (1395), alanine (1397), and valine (1394) for 3hrr protein, and glycine (1340), asparagine (1502), and arginine (1343) for 3hrq protein. Conclusion: Aflatoxins represent serious health risks due to their potent carcinogenic and hepatotoxic properties. The findings of this study revealed the inhibitory potential of morphine. Consequently, combinations of alkaloids with a central structure similar to morphine may be promising candidates as anti-aflatoxin agents, warranting further investigation and development for drug research.